2017
DOI: 10.1002/smi.2779
|View full text |Cite
|
Sign up to set email alerts
|

Dangers on the road: A longitudinal examination of passenger‐initiated violence against bus drivers

Abstract: This study examined the impact of workplace violence against 109 bus drivers over a 1-year span. Workplace violence is related to both psychological and work-related consequences. Our findings showed that bus drivers experienced a wide range of violence at work and the psychological consequences were devastating: Half of the participants met the diagnostic criteria for acute stress disorder within the first month following the index event. Majority of them experienced at least moderate levels of post-traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
1
11
0
3
Order By: Relevance
“…The prevalence of PTSD was found to be 12.6% (95% CI 9.5%-16.1%) among drivers surviving RTCs. The findings of this study are in line with one done in Canada among bus drivers (14.3%), 27 and also agree with a studies conducted among RTC survivors attending orthopedic and trauma clinics in Kenya (13.3%) 28 and Cape Town (12.2%). 29 However, the proportion in this study was lower than others among a group of Iranian commercial motor-vehicle drivers (19.2%), 14 survivors of RTCs in public hospitals in Addis Ababa (22.8%), 18 and Nigerians (26.7%).…”
Section: Prevalence Of Posttraumatic Stress Disordersupporting
confidence: 92%
“…The prevalence of PTSD was found to be 12.6% (95% CI 9.5%-16.1%) among drivers surviving RTCs. The findings of this study are in line with one done in Canada among bus drivers (14.3%), 27 and also agree with a studies conducted among RTC survivors attending orthopedic and trauma clinics in Kenya (13.3%) 28 and Cape Town (12.2%). 29 However, the proportion in this study was lower than others among a group of Iranian commercial motor-vehicle drivers (19.2%), 14 survivors of RTCs in public hospitals in Addis Ababa (22.8%), 18 and Nigerians (26.7%).…”
Section: Prevalence Of Posttraumatic Stress Disordersupporting
confidence: 92%
“…One possible explanation for not identifying the difference between ELAM scores as a function of sex is the small number of women participating in the survey when compared to the total number of male subjects. Another explanation is that a traditionally male organizational culture could encourage women not to complain about threats and aggressions (Zhou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…WB and aggressive behavior are frequent among collective transportation workers (Glasø, Bele, Nielsen and Einarsen 2011; Kornig, Chanut-Guieu, Domette, Louit-Martinod and Méhaut 2017; Lincoln and Gregory 2015; Zhou, Boyer and Guay 2018), being characterized by aggressions against mental and/or physical health. The safety and wellbeing of these workers are interconnected with the safety and wellbeing of passengers and other road users (Glasø et al 2011;Silveira, Abreu and Santos 2014;Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies show that exposure to OV increases risk of PTSD [18][19][20] . Further, extant literature has indicated that the frequency of OV might be a predictor of general mental health problems also, PTSD [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%